State contracting processes and institutional management: National Police of Peru - Saba Castañeda, Segundo Felix (2022)
The objective of this article was to analyze the incidence of State contracting processes in the institutional management of the National Police of Peru (PNP), 2014-2018. The research design was non-experimental, applied, correlational and analytical. The population consisted of 370 administrative and police personnel of the PNP Logistics Directorate. The sample comprised 188 workers of the PNP Logistics Directorate. The survey technique made data collection possible. The questionnaire was the fundamental tool together with the observation form instrument.  The research concludes that the contracting processes have a significant influence on the institutional management of the unit studied, which shows the relationship between the variables. In addition, it was shown that the contracting methods of the unit studied are efficient at a medium level due to the incidence of some procedures of regulations, norms, actions, laws, police personnel with little training and also, scarce intervention of the operative personnel.